Comprehensive Analysis of HDAC Family Identifies HDAC1 as a Prognostic and Immune Infiltration Indicator and HDAC1-Related Signature for Prognosis in Glioma - Fan, Yuxiang; Peng, Xinyu; Wang, Yubo; Li, Baoqin; Zhao, Gang (Frontiers in Molecular Biosciences, 2021)
Background: The histone deacetylase (HDAC) family restrained accessibility to chromatin containing tumor suppressor genes by removing acetyl groups, which was deemed a way of tumorigenesis. Considering glioma remained one of the most common brain cancers with dichotomy prognosis and limited therapy responses, HDAC inhibitors were an area of intensive researches. However, the expression profiles and prognostic value of the HDACs required more elucidation. Methods: Multiple biomedical databases were incorporated, including ONCOMINE, GEPIA, TCGA, CGGA, GEO, TIMER, cBioPortal, and Metascape to study expression profiles, prognostic value, immune infiltration, mutation status, and enrichment of HDACs in glioma. STRING and GeneMANIA databases were used to identify HDAC1-related molecules. LASSO regression, Cox regression, Kaplan-Meier plot, and receiver operating characteristic (ROC) analyses were performed for HDAC1-related signature construction and validation. Results: HDAC1 was significantly overexpressed in glioma, while HDAC11 was downregulated in glioblastoma. Except for HDAC 6/9/10, the HDAC family expression was significantly associated with glioma grade. Most of the HDAC family also correlated with glioma genetic mutations. Higher HDAC1 expression level predicted more dismal overall survival (OS) (p<0.0001) and disease-free survival (DFS) (p<0.0001), but a higher level of HDAC11 held more favorable OS (p= 2.1e−14) and DFS (p= 4.8e−08). HDAC4 displayed the highest mutation ratio 2.6% of the family. The prognostic value of HDAC1 was validated with ROC achieving 0.70, 0.77, 0.75, and 0.80 as separability for 1-, 3-, 5-, and 10-year OS predictions in glioma, respectively. Moreover, HDAC1 expression positively correlated with neutrophil (r=0.60, p=2.88e-47) and CD4+ T cell infiltration (r=0.52, p=3.96e-35) in lower-grade glioma. The final HDAC1-related signature comprised of FKBP3, HDAC1 (Hazard Ratio:1.49, 95%Confidence Interval:1.20-1.86), PHF21A, RUNX1T1, RBL1, and was verified by survival analysis (p<0.0001) and ROC with 0.80, 0.84, 0.83, and 0.88 as separability for 1-, 3-, 5-, and 10-year OS predictions, respectively. The signature was enriched in chromatin binding. Conclusion: HDAC family was of clinical significance for glioma. Most of the HDAC family significantly correlated with the glioma grade, IDH1 mutation, and 1p/19q codeletion. HDAC1 was both a prognostic and immune infiltration indicator and a central component of the HDAC1-related signature for precise prognosis prediction in glioma.